J02 Brain Training in HD: Enhancing Neural Plasticity using Real-time FMRI Neurofeedback Training. (17th September 2014) - Papoutsi, M; Weiskopf, N; Langbehn, DR; Reilmann, R; Rees, G; Tabrizi, SJ
Abstract : Background: Despite the absence of overt clinical symptoms, pre-symptomatic stages of Huntington's disease (HD) show marked atrophy in the striatum, accompanied by changes in neuronal function. To the extent that such changes in neuronal function support preserved behaviour, they are compensatory. Brain training can be used to support neural compensation by enhancing neural plasticity. Aims: The present study tests the feasibility of using real-time fMRI (rt-fMRI) neurofeedback training in HD. The aim is to restore brain function, as well as cognitive and motor performance, by training patients to regulate the activity of brain regions, such as the premotor cortex (PMC), whose function has been affected by the disease and is linked to cognitive and motor impairment. Methods: Early stage HD patients were trained to regulate their own brain activation using motor imagery and receiving near real-time, visual feedback on the level of their PMC activation (BOLD fMRI signal). Brain activation, as well as cognitive and motor capacity, was compared before and after training to establish training induced changes. Results: Patients who successfully learned to regulate their brain activation, showed an increase in their PMC activation from the first to the last visit. Increased PMC and motor network activation was also observed following training in an unrelated paced finger tapping task and in the absence of explicit neurofeedback. This was further accompanied by improvements in cognitive and motor performance. Conclusions: We provide preliminary evidence that rt-fMRI neurofeedback training can be used to induce neural re-organisation in HD and support motor and cognitive function. Because it is non-invasive and low-risk, it could be also used as an adjunctive treatment to other disease modifying therapies, such as cortical or striatal HTT gene-silencing, in order to enhance brain re-organisation and restore lost motor and cognitive function, following mutant HTT clearance.